Understanding the Genetics of Early-Onset Obesity in a Cohort of Children From Qatar - Idris Mohammed (751020) (2023)
Context Monogenic obesity is a rare form of obesity due to pathogenic variants in genes implicated in the leptin–melanocortin signaling pathway and accounts for around 5% of severe early-onset obesity. Mutations in the genes encoding the MC4R, leptin, and leptin receptor are commonly reported in various populations to cause monogenic obesity. Determining the genetic cause has important clinical benefits as novel therapeutic interventions are now available for some forms of monogenic obesity. Objective To unravel the genetic causes of early-onset obesity in the population of Qatar. Methods In total, 243 patients with early-onset obesity (above the 95% percentile) and age of onset below 10 years were screened for monogenic obesity variants using a targeted gene panel, consisting of 52 obesity-related genes. Results Thirty rare variants potentially associated with obesity were identified in 36 of 243 (14.8%) probands in 15 candidate genes (LEP, LEPR, POMC, MC3R, MC4R, MRAP2, SH2B1, BDNF, NTRK2, DYRK1B, SIM1, GNAS, ADCY3, RAI1, and BBS2). Twenty-three of the variants identified were novel to this study and the rest, 7 variants, were previously reported in literature. Variants in MC4R were the most common cause of obesity in our cohort (19%) and the c.485C>T p.T162I variant was the most frequent MC4R variant seen in 5 patients. Conclusion We identified likely pathogenic/pathogenic variants that seem to explain the phenotype of around 14.8% of our cases. Variants in the MC4R gene are the commonest cause of early-onset obesity in our population. Our study represents the largest monogenic obesity cohort in the Middle East and revealed novel obesity variants in this understudied population. Functional studies will be required to elucidate the molecular mechanism of their pathogenicity. Other Information Published in: The Journal of Clinical Endocrinology & Metabolism License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1210/clinem/dgad366